2020
DOI: 10.1108/nfs-02-2020-0048
|View full text |Cite
|
Sign up to set email alerts
|

Snacking, sugar-sweetened beverage consumption and child obesity in low-income households

Abstract: Purpose Snacking contributes to one-quarter of children’s total daily energy intake in the USA, with many snack foods being nutrient-poor and energy-dense. Snacking and sugary beverage consumption have been identified as potential contributors to childhood overweight and obesity and may play a particularly important role among children from socioeconomically disadvantaged households that generally display higher rates of obesity. This exploratory study investigated associations between consumption of snack foo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 34 publications
1
10
0
1
Order By: Relevance
“…, 2011). Indeed, in another study examining the consumption of sweet snacks, salty snacks and sugary drinks in low-income families, the results show that there is no association between the consumption of snacks or sugary drinks and excess weight in children (Walsh et al. , 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…, 2011). Indeed, in another study examining the consumption of sweet snacks, salty snacks and sugary drinks in low-income families, the results show that there is no association between the consumption of snacks or sugary drinks and excess weight in children (Walsh et al. , 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a study shows that there is a significant negative association between three consumption variables (sweet treats, salty snacks, and sugary drinks) and household income (Walsh et al. , 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ashi et al (2019) have reported no significant correlation between the dietary habits and the BMI of a group Saudi schoolchild. In contrary, Walsh et al (2020) have reported that snacking and sugary beverage consumption have been identified as potential contributors to childhood overweight and obesity (Walsh et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In several countries, approximately 60% of the daily caloric intake of children came from ultra-processed foods, and the primary and secondary school environment were one of the main places of consumption of this type of products because of the accessible acquisition of ready-to-eat meals (Khandpur et al, 2020). Moreover, increased consumption of ultraprocessed foods was correlated with socioeconomic level, as low-income households had a higher registered consumption of cheaper and less nutritious foods (Matos et al, 2021;Walsh et al, 2021). Therefore, adoption of healthier dietary patterns should help reintroduce the ingestion of good-quality components, such as fibre, complex carbohydrates and unsaturated fats, thus displacing the aforementioned undesirable ones from diets.…”
Section: Children's Nutritional Statusmentioning
confidence: 99%